The role of doulas in abortion care in Canada: A qualitative study - Martha Paynter; Clare Heggie; Anja McLeod; Mélina Castonguay; Melissa Fuller; Wendy V. Norman (PLoS ONE, 2025)
Introduction Equitable and safe access to abortion is essential for reproductive autonomy. Despite decriminalization in 1988, barriers to accessing abortion in Canada persist, particularly for people in underserved groups. Doulas, working in a non-clinical and unregulated supportive role, may facilitate access to family planning services, but evidence about the scope, role, training, and efficacy of doulas in abortion care is lacking. The goal of this study was to understand the experience of abortion doulas in Canada with respect to their role and facilitators and challenges faced in practice. Method For this community-based, qualitative national study of abortion doula practice, we first created a national directory of all doulas in Canada in 2023 using publicly available online information. From this directory, we extracted contact information for doulas who indicated they provide abortion support and sent invitations for a one-time qualitative interview. Questions addressed current role and responsibilities, gaps in doula training and knowledge, and challenges and opportunities they perceived with respect to client support. We used reflexive thematic analysis to generate key themes. Our research team includes abortion doula experts. Results Among 73 abortion doulas with public listings in Canada in 2023 to whom we sent invitations, 15 completed an interview. We developed six key themes: Inter and intra-systems navigation; After-care; In over their heads; Balancing act; Support for the supporter; and Beyond the individual. Abortion doulas navigate fragmented systems and support clients experiencing intersecting forms of oppression and exclusion. These complex logistics include locating care providers, securing transportation, and obtaining funds for clients’ out-of-pocket costs. Doulas faced challenges acquiring adequate training, understanding local health systems, forging relationships and supporting clients facing structural barriers to care. Abortion doula work is facilitated by peer and organizational support, connections to clinics and providers, and comprehensive and contextually appropriate training. Conclusions Abortion doulas express needs for comprehensive, evidence-based training, meaningful partnerships and sustainable remuneration. Future research should explore abortion provider and clinic staff perspectives with respect to the potential role of doulas in wrap-around client support services.